2022
DOI: 10.1097/scs.0000000000008771
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells in Temporomandibular Joint Engineering: State of Art and Future Persectives

Abstract: Temporomandibular joint (TMJ) osteoarthritis is a degenerative disease, characterized by gradual cartilage degradation, bone remodeling, synovitis, and chronic pain. Due to the limited self-healing capacity in condylar cartilage, traditional clinical therapy have limited symptom-modifying and structure-modifying effects to restore impaired cartilage as well as other TMJ tissues. In last years, stem cell-based therapy has collected much attention as a possible approach toward tissue repair and regeneration. Mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…Considering pain as one of the most problematic consequences of SB, Ferrillo et al have reported, based on a conducted meta-analysis, that conservative approaches including rehabilitative therapies (like splint appliance and laser therapy) might be effective in the treatment of pain in TMJ disorders [ 6 ]. New treatment methods are emerging, among them regeneration of TMJ with the use of mesenchymal stem cells [ 7 ]. In the global novel problem of the COVID-19 pandemic, even some modern teledentistry approaches have been suggested as applicable in the treatment of TMJ disorders [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering pain as one of the most problematic consequences of SB, Ferrillo et al have reported, based on a conducted meta-analysis, that conservative approaches including rehabilitative therapies (like splint appliance and laser therapy) might be effective in the treatment of pain in TMJ disorders [ 6 ]. New treatment methods are emerging, among them regeneration of TMJ with the use of mesenchymal stem cells [ 7 ]. In the global novel problem of the COVID-19 pandemic, even some modern teledentistry approaches have been suggested as applicable in the treatment of TMJ disorders [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the multifactorial etiology of TMD, several treatment strategies have been adopted and the choice of these varies according to the degree of severity of the disorder [ 11 ]. Preferably, more conservative methods have been chosen as the first line of treatment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preferably, more conservative methods have been chosen as the first line of treatment [ 12 ]. Among these, we can mention non-invasive ones such as patient education, pharmacotherapy, physiotherapy, interocclusal splints, prosthetic rehabilitation, and/or minimally invasive such as arthrocentesis, hyaluronic acid injections, intra-articular injections of corticosteroids, platelet-rich plasma (PRP), oxygen–ozone therapy, and arthroscopy [ 11 , 12 , 13 , 14 ]. In some cases considered as severe, when patients do not respond to the conservative treatments, more invasive and intra-articular surgical interventions are required [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it can increase requests for analgesic medications and length of hospital stay [15,16]. Moreover, the level of perceived anxiety before childbirth is signifcantly associated with postpartum hemorrhage [17], postpartum bruxism, and temporomandibular disorder [18][19][20][21][22]. Women's mental state can have adverse efects on the fetus leading to fetal asphyxia, abnormal fetal heart rate patterns, low Apgar scores, and increased mortality [23].…”
Section: Introductionmentioning
confidence: 99%